The level of stress among students in urban and rural secondary schools in Malaysia. - Sulaiman, Tajularipin; Hassan, Aminuddin; M. Sapian, Vizata; Abdullah, Saifuddin Kumar (EuroJournals, Inc., 2009)
The purpose of this study was to determine the relationships between stress level and academic achievement among students in urban and rural secondary schools in of the district in Malaysia. A study of stress, especially an approach towards measuring level of stress among adolescents is quite new in Malaysia. So, an attempt to study this condition, starting with normal adolescents, is the purpose of this study. This study had three main objectives. The first objective was to find the total percentage of students who suffered high stress, medium stress and low stress. The second objective was to compare the stress level between gender and the third objective was to compare the stress level between students from urban and rural area. The subjects of the study comprised of 155 Form Four students from two secondary schools in Malaysia. This study used the survey method by administering Students-life Stress Inventory (SSI) questionnaires. The study showed that no students experienced high stress, 29 percent students experienced medium stress and 71 percent students experienced low stress. Using the t-test, the findings of the study also indicated that there are significant differences in level of stress for gender and between students in rural and urban secondary school. A general conclusion is that there are many factors influences students' stress such as parenting style, parents education background, environment of the students which is can give impact in students life.